Charting the elements of pedagogic frailty. Issue 1 (2nd January 2016) - Kinchin, I.M.; Alpay, E.; Curtis, K.; Franklin, J.; Rivers, C.; Winstone, N.E.
Abstract: Background: The concept of pedagogic frailty has been proposed as a unifying concept that may help to integrate institutional efforts to enhance teaching improvement within universities by helping to maintain a simultaneous focus on four key areas that are thought to impede development.Purpose: The variation in internal structure of the four dimensions of pedagogic frailty and the links that have been proposed to connect them are explored here through the analysis of interviews with academics working in a variety of disciplinary areas.Methods: The application of concept map-mediated interviews allows us to view the variable connections within and between these dimensions and the personal ways they are conceptualised by academics working across the heterogeneous university context.Results: The data show that academics conceptualise the discourse of teaching in various ways that have implications for the links that may be developed to integrate the elements within the model.Conclusions: Whilst the form and content of the maps representing dimensions of the pedagogic frailty model exhibit considerable variation, it is suggested that factors such as academic resilience and the explicit use of integrative concepts within disciplines may help to overcome some of the vulnerabilities that accompany pedagogic frailty. The data also raises questions about the links between factors that tend to be under individual control and those that tend towards institutional control.